2015
DOI: 10.5039/agraria.v10i3a5165
|View full text |Cite
|
Sign up to set email alerts
|

Divergência genética e importância de caracteres em genótipos de batata-doce visando a produção de silagem

Abstract: RESUMOAtentando-se à necessidade de adoção de sistemas agrícolas mais sustentáveis, é importante que os programas de melhoramento de batata-doce procurem aumentar além da produtividade de raízes a produtividade e a qualidade de ramas para a produção de silagem. Objetivou-se avaliar a divergência genética e a importância de caracteres associados à produção e qualidade de silagem de ramas em genótipos batata doce. O experimento foi conduzido no Campus JK da Universidade Federal dos Vales do Jequitinhonha e Mucur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
(15 reference statements)
0
7
0
1
Order By: Relevance
“…Among the advantages of using multivariate analysis techniques, we highlight the possibility of evaluating the importance of each characteristic studied in the estimation of dissimilarity (Azevedo et al, 2015). Thus, based on the criterion proposed by Singh (1981), in terms of relative contribution, it was evidenced greater importance for the characteristics of the vitamin A content, starch content, total soluble sugars, nonreducing sugars, antioxidant potential, pulp fresh mass, plant height and fresh fruit mass.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Among the advantages of using multivariate analysis techniques, we highlight the possibility of evaluating the importance of each characteristic studied in the estimation of dissimilarity (Azevedo et al, 2015). Thus, based on the criterion proposed by Singh (1981), in terms of relative contribution, it was evidenced greater importance for the characteristics of the vitamin A content, starch content, total soluble sugars, nonreducing sugars, antioxidant potential, pulp fresh mass, plant height and fresh fruit mass.…”
Section: Resultsmentioning
confidence: 89%
“…Brandão et al (2013) found that the elimination of some descriptors, such as fruit diameter, leaf blade length, petiole length and pseudostem diameter, used to characterize the banana germplasm, did not cause loss of information for the formation of the groups formed in 77 banana tree accesses evaluated. According to Brandão et al (2013) and Azevedo et al (2015), the analysis of less important characteristics for the study of divergence is not necessary in future studies, which reduces labor costs, cost of analysis and time. Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hybrids 12 and 15 were grouped within the maximum classification reference because they presented higher values for the evaluated vegetative and anatomical traits (Figure 1), being also classified into different groups by the Tocher method (Table 5 Notably, studies have pointed out the importance of using different methodologies to evaluate genetic variability aiming to ensure higher reliability of results (Azevedo et al, 2013(Azevedo et al, , 2015 and consistency in the clustering pattern (Nascimento et al, 2014). In fact, this criterion has been observed in studies aimed at characterizing the genetic variability among coffee genotypes to select superior materials for desired traits Notably, studies have pointed out the importance of using different methodologies to evaluate genetic variability aiming to ensure higher reliability of results (Azevedo et al, 2013(Azevedo et al, , 2015 and consistency in the clustering pattern (Nascimento et al, 2014). In fact, this criterion has been observed in studies aimed at characterizing the genetic variability among coffee genotypes to select superior materials for desired traits (Covre et al, 2016;W.…”
Section: Estimates Of the Relative Contribution Of Anatomical And Vegetative Traits To Geneticmentioning
confidence: 99%